1996
DOI: 10.1111/j.1399-6576.1996.tb04521.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein binding of propofol in patients with renal failure or hepatic cirrhosis

Abstract: Due to the absence of significant changes in the protein binding it is unlikely that there will be an exaggerated pharmacological response in patients with renal and hepatic disease following the administration of a standard propofol dose, although due to interpatient variability careful titration can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Experimental measurements of the normal human free plasma propofol fraction (freepl) fall into two different ranges. The smaller value of about 0.01 comes from a series of publications by Suarez and colleagues using ultrafiltration [14-16]. A larger value of about 0.02 has been reported by several other research groups: Using equilibrium dialysis, Altmayer et.…”
Section: Methodsmentioning
confidence: 96%
“…Experimental measurements of the normal human free plasma propofol fraction (freepl) fall into two different ranges. The smaller value of about 0.01 comes from a series of publications by Suarez and colleagues using ultrafiltration [14-16]. A larger value of about 0.02 has been reported by several other research groups: Using equilibrium dialysis, Altmayer et.…”
Section: Methodsmentioning
confidence: 96%
“…3134 The dose of propofol used clinically in children varies widely but typically ranges from about 1–10 μg/mL (blood concentration) with higher doses used for induction of anesthesia and lower doses used for maintenance. 3537 In addition, cell culture and whole animal studies have shown that propofol can induce toxicity at high doses or prolonged exposure times after a single exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, there have been only a few studies on the pharmacokinetics and safety of sedation in patients with end-stage liver disease [2][3][4][5][6][7][8][9][10]. Midazolam may precipitate overt hepatic encephalopathy (OHE) or minimal hepatic encephalopathy (MHE), but cases of OHE requiring intervention after an endoscopic procedure are unusual in clinical practice.…”
Section: Introductionmentioning
confidence: 99%